Aziatex Global Sdn Bhd / Muhammad Aqil Najmi Mohd Naim - Mohd Naim, Muhammad Aqil Najmi (Faculty of Business and Management, 2023)
I am Muhammad Aqil Najmi Bin Mohd Naim holding matric card number of 2020819382 and majoring in Bachelor of Business Administration (Hons.) Marketing at Faculty of Business and Management. I have experienced industrial training for 24 weeks starting from 1 March 2023 until 15 August 2023.1 have carrying out industrial training in an organization located in Kuantan Pahang which is Axiatex Global Sdn. Bhd. whose address is No 9, Mahkota Valley Office, NO. A, 103, Jalan IM9/4, Bandar Indera Mahkota, 25200 Kuantan, Pahang. First of all, I've included my most recent updated resume with this application to Aziatex Global Sdn Bhd. In addition, I gathered basic information on Aziatex Global Sdn Bhd, such as their opening and closing times, goals, history, and organizational structure. My supervisor's reaction, Mrs. Hazliza Binti Jusoh, and the corporate website served as the foundation for what I learnt. There are two locations for Aziatex Global Sdn Bhd in Kuantan and Kuala Lumpur. Aziatex Global Sdn Bhd is a firm that provides services. Businesses like Seri Wajah Muslimah Aesthetic, Makcik Unit Muslimah Spa, Nieza Salon, Pen and Pepper Cafe, and Ummy Wax are clients of Aziatex Global Sdn Bhd. Through my internship, I gained a lot of experience, information, and skills. I was able to start my own self-exploration through this internship program, improve my communication and problem-solving skills, and get experience in a real working setting. I discussed the SWOT analysis with someone and offered some suggestions for how Aziatex Global Sdn Bhd may enhance its products and services. The internship program, in my opinion, was generally effective in accomplishing its goals and giving students a worthwhile learning opportunity before entering the real working world.